Pengaruh Motivasi Kerja, Komitmen Organisasi Dan Pengembangan Terhadap Kinerja Pegawai Badan Pengelola Keuangan Dan Aset Kabupaten Serdang Bedagai - Suci Hardiyanti; Sintong Naek Halashon Hutasoit; Sumuntul Martahan H. Sipahutar; Siwan; Uti Pennia; Nilawati Nasti; Neni Sriwahyuni (Forum Kerjasama Pendidikan Tinggi, 2023)
This formula research internal issue is how influence job motivation on employees performance. How influence of organization coomitment xx on employees performance. How influence of development on employees performance. How influence of job motivation, organization coomitment, and development on employees performance. This research target is to for know influence and analyze of job motivation on employees performance. For know influence and analyze of organization coomitment on employees performance. For know influence and analyze development on employees performance. For know influence and analyze job motivation, organization coomitment and development on employees performance. Sample in this research amount to 39 employees. Technique analyze data which used in this research is analysis of regresi multiple linear. This research result explain of job motivation effect positive and significant on employees performance. Organization coomitment effect positive and significant on employees performance. Development effect positive and do not significant on employees performance. Job motivation, organization coomitment, and development effect and positive and significant on employees performance.